2014
DOI: 10.5301/hipint.5000135
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Femoroacetabular Impingement: Minimum Five-Year Follow-up

Abstract: Arthroscopic treatment of femoroacetabular impingement, at five years follow-up, revealed good results in terms of improved function, pain relief and satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…The mean postsurgery follow-up was 28.1±15.5 months in 89% of studies that reported this variable. Follow-up ranged from 12 months25 28 to 73.2 months 49…”
Section: Resultsmentioning
confidence: 99%
“…The mean postsurgery follow-up was 28.1±15.5 months in 89% of studies that reported this variable. Follow-up ranged from 12 months25 28 to 73.2 months 49…”
Section: Resultsmentioning
confidence: 99%
“…[ 43 ] USA Case series IV 153 47% 57 (50–77) 35.7 (12–64) months Arthroscopy 9 Polesello et al. [ 44 ] Brazil Case series IV 24(26) 87.5% 34 (13–51) 6.1 (5–8) years Arthroscopy 7 Singh et al. [ 45 ] Australia Case series IV 24(27) 100% 22 (16–29) 22 (6–60) months Arthroscopic 10 Sink et al.…”
Section: Resultsmentioning
confidence: 99%
“…Hip arthroscopy has been used for a long time to effectively treat femoral and acetabular deformities (cam and pincer, respectively), and repair injuries of the acetabular labrum and adjacent cartilage (10)(11)(12). In many studies, hip arthroscopy has been reported to have poor clinical outcomes when performed in patients with advance OA (13).…”
Section: Discussionmentioning
confidence: 99%